Characterization of desired catfish products and related challenges faced by farmer producers in Oyo, Ogun, and Delta states, Nigeria - Komugisha, Basiita Rose; Manyise, Timothy; Mwema, Catherine; Cole, Steven; Oyesola, Olutokunbo; Akuwa, Elizabeth; Fregene, Bernadette; Siriwardena, Sunil; Rossignoli, Cristiano; Benzie, John (2023)
The dataset includes transcripts of focus groups discussion conducted with catfish farmers in Oyo, Delta and Ogun State, with the project goal of characterizing catfish products desired by farmers in Nigeria in view of a catfish genetic improvement program.